2016
DOI: 10.1002/adem.201600216
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Reinforcement Distribution and Interface on the Electronic Transport Properties of MWCNT‐Reinforced Metal Matrix Composites

Abstract: The transition toward an electricity-driven world is testing electrical contact materials to their limits. Specifically, new alternatives are needed where composites that sacrificed conductivity in exchange for reduced weldability and higher heat dissipation sufficed. Carbon nanotubes (CNT) have the potential to close the gap as ideal fillers due to their outstanding intrinsic properties, pushing the application limits further. However, the reported electrical conductivity measurements show no clear tendency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Metals 2020, 10, 2 2 of 13 Although there are diverse production techniques, powder metallurgy (PM) is considered one of the most efficient, and is often used to produce these nanocomposites [42][43][44][45][46]. This method is based upon four fundamental steps: manufacturing the powder(s), mixture and dispersion of the reinforcement particles and the matrix metallic powders, pressing of the powders to form compacts, and sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Metals 2020, 10, 2 2 of 13 Although there are diverse production techniques, powder metallurgy (PM) is considered one of the most efficient, and is often used to produce these nanocomposites [42][43][44][45][46]. This method is based upon four fundamental steps: manufacturing the powder(s), mixture and dispersion of the reinforcement particles and the matrix metallic powders, pressing of the powders to form compacts, and sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcing copper coatings by dispersing nanoparticles within the metal matrix has shown some promise in improving its physical and mechanical characteristics in engineering applications. [15][16][17][18][19][20][21][22] Such nanoparticle-reinforced copper matrix composites have provided routes for improving mechanical and tribological resistance, enhancing electrical and thermal performance and promoting anticorrosion mechanisms. Reinforced copper matrix composites that incorporate the graphene family of nanomaterials are of particular interest for use in tribology.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the likelihood of switch welding is considerably reduced when CNT are present in the system, even at elevated current levels. Moreover, multiple studies have reported that the addition of CNT as a reinforcement phase in nickel matrices has significantly reduced friction and wear [21][22][23], as well as CNT coatings providing wear protection while having a marginal impact on ECR [24][25][26]. Furthermore, the incorporation of CNT into the system could provide the electrical switch with secondary advantages due to the chemical inertness and hydrophobic wetting behavior of this carbon nanostructure [27][28][29], in addition to their exceptional mechanical properties [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%